Global Health, Participation, and Empowerment: Decolonising’ Global Health - Tegama, Natalie (Jahrbuch für Christliche Sozialwissenschaften, 2024)
As often happens with concepts that traverse the academy and popular culture, decol-onisation has become a buzzword and, in the process, it has amassed new meanings. It has therefore become increasingly important to situate the decolonisation debate, including within the global health space. In this brief chapter, we introduce the colonial/decolonial duality, and offer conceptual clarification alongside problematising the current structures and barriers to participation for previously colonised communities. We then highlight the need to dismantle structures that are grounded on and uphold coloniality and suggest pathways towards rebuilding a more equitable global health space through employing the principle of subsidiarity. To this end, we propose a frame-work that is imagined as a deliberative and dialogic tool that can be instrumental for actors within the global health space to navigate their way towards decolonial futures.